THE ONLINE SENSORIAL EVALUATION OF FOOD - Triatma, Bambang (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2017)
One of the subjects in the vocational education is the analysis of the food quality by sensorial evaluation. The sensorial evaluation of food is usually done by humans in a laboratory where used